2014
DOI: 10.1186/1471-2407-14-356
|View full text |Cite
|
Sign up to set email alerts
|

CA15-3 is a useful serum tumor marker for diagnostic integration of hybrid positron emission tomography with integrated computed tomography during follow-up of breast cancer patients

Abstract: BackgroundThe aim of this study was to evaluate the value of CA15-3 for the diagnostic integration of molecular imaging findings performed with hybrid positron emission tomography and computed tomography (PETCT) technology.MethodsWe retrospectively selected 45 patients with a median age of 60 years (range 39–85 years) and a previous history of breast cancer (BC) who had already been treated with surgery and other treatments. Three measurements of CA15-3 were collected within 1 year before PETCT examination, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Moreover, our results showed that follow-up 18 F-FDG PET/CT scans with other different indications, including prior clinical suspicion of tumor recurrence, prior rising tumor marker or abnormal laboratory tests suggesting recurrence, prior rising tumor markers or abnormal laboratory tests, therapy response assessment of recurrence, intratherapy assessment of recurrence, and follow-up scanning to assess the previous equivocal response, led to a change in the management of patients in 20%-40% of scan times. Previous studies also evaluated the value of 18 F-FDG PET/CT imaging after rising tumor markers or clinical suspicion of tumor recurrence, concluding that 18 F-FDG PET/CT is a good noninvasive imaging modality in these 2 settings to confirm or rule out tumor recurrences (4,12,29,30). Also, multiple studies confirmed the value of 18 F-FDG PET/CT scan in the therapy assessment setting after chemoradiation therapy in several cancer types (31)(32)(33).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, our results showed that follow-up 18 F-FDG PET/CT scans with other different indications, including prior clinical suspicion of tumor recurrence, prior rising tumor marker or abnormal laboratory tests suggesting recurrence, prior rising tumor markers or abnormal laboratory tests, therapy response assessment of recurrence, intratherapy assessment of recurrence, and follow-up scanning to assess the previous equivocal response, led to a change in the management of patients in 20%-40% of scan times. Previous studies also evaluated the value of 18 F-FDG PET/CT imaging after rising tumor markers or clinical suspicion of tumor recurrence, concluding that 18 F-FDG PET/CT is a good noninvasive imaging modality in these 2 settings to confirm or rule out tumor recurrences (4,12,29,30). Also, multiple studies confirmed the value of 18 F-FDG PET/CT scan in the therapy assessment setting after chemoradiation therapy in several cancer types (31)(32)(33).…”
Section: Discussionmentioning
confidence: 94%
“…The mission coincides with the institutional role (recognized by the Italian Ministry of Health) of the IRCCS SDN, which is to optimize and improve scientific knowledge in the field of in vivo and in vitro diagnostic integration [1,2]. The IRCCS SDN is equipped with cutting-edge technologies that include positron emission tomography with integrated computed tomography (PET/CT) and PET with integrated magnetic resonance imaging (PET/MRI).…”
mentioning
confidence: 87%
“…Early studies suggested that it had limited sensitivity in the diagnosis of breast cancer, 28 but a recent study evaluating the value of CA15-3 for the diagnostic integration of molecular imaging findings performed with hybrid PET/CT technology, found that serial increases in CA15-3 could be used to predict positive PET/CT results. 38 Following early clinical data supporting the use of the tumor marker CA27.29 in monitoring therapeutic response, 39 Recently, panels of autoantibodies discovered by Drs Anderson and LaBaer have led to the exciting prospect of a screening test that incorporates many autoantibodies, each with a specificity of 80-90 %. 39 In order to increase the predictive value of tumor-specific autoantibodies for use as immunodiagnostics, this research has focused on testing multiple antigens in parallel.…”
Section: Potential Biomarkers In Breast Cancer Screeningmentioning
confidence: 99%